1997
DOI: 10.1136/gut.40.4.516
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of oestrogen receptor and oestrogen inducible genes in gastric mucosa and cancer.

Abstract: Background-Evidence exists for a role

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 22 publications
(5 reference statements)
2
20
2
Order By: Relevance
“…Our findings support those of Wu et al (1992a), finding no significant difference in ER or PR expression in gastric cancer compared with normal gastric mucosa using DCC and EIA assays. This is in contrast to the data reported by Kojima et al (1991) which demonstrated expression of ER in gastric cancer, but not in normal mucosa when measured by immunohistochemistry and recent data from Singh et al (1997) showing decreased expression of ER in gastric cancer compared to normal mucosa. Our data showed no significant difference between receptor-positive and receptor-negative groups on comparison with sex, tumour grade and tumour stage.…”
Section: Discussioncontrasting
confidence: 56%
“…Our findings support those of Wu et al (1992a), finding no significant difference in ER or PR expression in gastric cancer compared with normal gastric mucosa using DCC and EIA assays. This is in contrast to the data reported by Kojima et al (1991) which demonstrated expression of ER in gastric cancer, but not in normal mucosa when measured by immunohistochemistry and recent data from Singh et al (1997) showing decreased expression of ER in gastric cancer compared to normal mucosa. Our data showed no significant difference between receptor-positive and receptor-negative groups on comparison with sex, tumour grade and tumour stage.…”
Section: Discussioncontrasting
confidence: 56%
“…Our findings support those of , finding no significant difference in ER or PR expression in gastric cancer compared with normal gastric mucosa using DCC and EIA assays. This is in contrast to the data reported by Kojima et al (1991) which demonstrated expression of ER in gastric cancer, but not in normal mucosa when measured by immunohistochemistry and recent data from Singh et al (1997) showing decreased expression of ER in gastric cancer compared to normal mucosa. Our data showed no significant difference between receptor-positive and receptor-negative groups on comparison with sex, tumour grade and tumour stage.…”
Section: contrasting
confidence: 56%
“…A male preponderance (Furukawa et al, 1982a) and a protective effect of female hormones have been reported for stomach cancer in rat experimental models (Furukawa et al, 1982b). As functional oestrogen receptors alpha (Wu et al, 1990;Singh et al, 1997) and beta (Taylor and Al-Azzawi, 2000;Matsuyama et al, 2002) exist in human stomach mucosa, it has been hypothesised that sex hormones, notably oestrogens, protect women against stomach cancer (Sipponen and Correa, 2002).…”
mentioning
confidence: 99%